IS EARLY CLOSURE OF STOMA WARRANTED IN THE MANAGEMENT OF TEMPORARY LOOP ILEOSTOMY? - Khan, Nadim; Bangash, Adil; Hadi, Ainul; Ahmad, Munir; Sadiq, Muzaffaruddin (Journal of Postgraduate Medical Institute, 2011)
Objective: Methodology: Results: Conclusion: Apart from wound infection the frequency of complication following early closure (4 weeks) of temporary loop stoma is similar to delayed closure. Thus delayed closure of stomae should be abandoned. Group A included 155 patients and Group B 156 patient with male predominance in both groups (p=0.869). The mean age in both groups was similar 33.6 years and 32.7 years respectively. Anastamotic leak rate and wound dehiscence was lower in early closure group but p value was insignificant. The frequency of wound infection was higher in the early stoma closure group (p=0.001). The mean hospital stay was similar. This was an experimental study conducted at the surgical A unit of Lady Reading Hospital Between Jan 2005 and Dec 2009. All patients who were primarily operated and ended up with temporary loop ileostomy were admitted via the out-patient department. Consecutively allocated into group A whose stomae were closed at 8 weeks and group B whose stomae closed at 4 weeks. Postoperative complications including wound infection, anastamotic leak, dehiscence etc. were recorded and statistical analysis done using version 13.0 SPSS for windows. To assess the outcome of closure of temporary loop ileostomies by comparing frequency of post operative complication.